First principle investigation on hydrogen solid storage in Zr1-xNbxNiH3 (x = 0 and 0.1). (30th August 2019) - Rkhis, M.; Alaoui-Belghiti, A.; Laasri, S.; Touhtouh, S.; Hajjaji, A.; Hlil, E.K.; Bessais, L.; Soubane, D.; Zaidat, K.; Obbade, S.
Abstract: We study hydrogen storage properties of Nb doped ZrNiH3 using the first-principles calculations based on density functional theory (DFT). To achieve such calculations, we used full potential linearized augmented plane waves (FP-LAPW) method implanted in WIEN2K code. Total energy and density of states (DOS) are computed for Zr1-x Nbx NiH3 (x = 0 and 0.1). It turns out that substituting 10% of zirconium by niobium in ZrNiH3 matrix involves a destabilization of the system. This destabilization is induced by the formation of a new hybridization between niobium and hydrogen atoms. Furthermore, the thermodynamic stability in terms of its energy of formation, as well as the capacity of the material to store hydrogen are discussed. Noteworthy that from FP-LAPW we report that Nb doped ZrNiH3 lower the desorption temperature to 305.77 K without significant reduction of the hydrogen storage capacity. This lowering of the temperature desorption makes the material very useful for hydrogen storage in solids. Highlights: Structure and stability of ZrNiH3 doped with Nb has been studied using ab initio simulation. The energy of formation is closer to the required value −40 kJ/mol.H2 for hydrogen application. The temperature of desorption decreases without affecting the storage capacities.